Circulating Tumor Cells as a Promising Tool for Early Detection of Hepatocellular Carcinoma - Mahsa Salehi; Zohre Miri Lavasani; Hani Keshavarz Alikhani; Bahare Shokouhian; Moustapha Hassan; Mustapha Najimi; Massoud Vosough (Cells, 2023)
Liver cancer is a significant contributor to the cancer burden, and its incidence rates have recently increased in almost all countries. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and is the second leading cause of cancer-related deaths worldwide. Because of the late diagnosis and lack of efficient therapeutic modality for advanced stages of HCC, the death rate continues to increase by ~2–3% per year. Circulating tumor cells (CTCs) are promising tools for early diagnosis, precise prognosis, and follow-up of therapeutic responses. They can be considered to be an innovative biomarker for the early detection of tumors and targeted molecular therapy. In this review, we briefly discuss the novel materials and technologies applied for the practical isolation and detection of CTCs in HCC. Also, the clinical value of CTC detection in HCC is highlighted.